2020
DOI: 10.12688/wellcomeopenres.15633.2
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a single-centre observational study of household wellbeing and poverty status following a diagnosis of advanced cancer in Blantyre, Malawi - ‘Safeguarding the Family’ study

Abstract: Background: Many households in low-and-middle income countries face the additional burden of crippling out-of-pocket expenditure when faced with a diagnosis of life-limiting illness. Available evidence suggests that receipt of palliative care supports cost-savings for cancer-affected households. This study will explore the relationship between receipt of palliative care, total household out-of-pocket expenditure on health and wellbeing following a first-time diagnosis of advanced cancer at Queen Elizabeth Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Subsequently, a retrospective cohort study in diabetic adults reported the therapeutic potential of MET to reduce severe forms of dengue disease 22 . Also, MET currently being tested as adjunctive therapy for dengue in overweight and obese patients 23 . Therefore, this article has focused on studying the potential of MET to inhibit in vitro and in vivo ZIKV infection, comparing it with its anti-DENV effect.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a retrospective cohort study in diabetic adults reported the therapeutic potential of MET to reduce severe forms of dengue disease 22 . Also, MET currently being tested as adjunctive therapy for dengue in overweight and obese patients 23 . Therefore, this article has focused on studying the potential of MET to inhibit in vitro and in vivo ZIKV infection, comparing it with its anti-DENV effect.…”
Section: Introductionmentioning
confidence: 99%